RETHINKING THE 4A MODEL IN COASTAL TOURISM: WHY ACCESSIBILITY MATTERS MORE THAN ATTRACTIONS FOR REVISIT INTENTION - Bimo Kuncoro Jati; riswano; Rachmadina Rafika Triani; Candra Karismawan (Family Welfare Education, 2026)
This study reexamines the structural relevance of the 4A tourism supply model (Attraction, Accessibility, Amenities, and Ancillary Services) in explaining revisit intention within emerging coastal destinations. While prior research frequently emphasizes attraction quality as the primary determinant of tourist loyalty, limited empirical attention has been given to the relative dominance of structural supply components in peripheral coastal contexts. This research aims to analyze the influence of the 4A components on revisit intention and identify the most dominant predictor in Ngrenehan Beach, Gunung Kidul Regency, Indonesia. A quantitative explanatory design was employed using a survey of 120 domestic tourists. Data were analyzed through multiple regression and structural modeling procedures to test direct effects among constructs. The findings reveal that although the 4A components collectively influence revisit intention, accessibility is the only variable with a statistically significant positive effect. Attraction, amenities, and ancillary services do not independently predict revisit intention. The model explains 70.4% of the variance in revisit intention, indicating strong explanatory power. These results suggest that in emerging coastal destinations, accessibility functions as a structural enabler that conditions the effectiveness of other tourism supply elements. The study contributes theoretically by refining the 4A framework through contextual dominance analysis and offers practical implications for destination managers to prioritize transportation connectivity and infrastructure development as strategic levers for enhancing tourist loyalty and long term competitiveness.